Pengaruh Penghargaan Dan Sanksi Terhadap Kinerja Karyawan Pada PT. Iss Indonesia Area Indofood Kota Tangerang - Rivaldi, Achmad; Sudarso, Eko (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study is to determine the reward and punishment on employee performance at PT ISS Indonesia Area Indofood kota tangerang, both partially and simultaneously. The research method used in this study is quantitative research. The population in this study consists of employees of PT ISS Indonesia, Indofood Area, Tangerang City. The sampling technique used in this study is the saturated sampling method, in which the entire population of 70 employees is taken as the sample. The data collection method used in this study is primary data. The primary data were obtained from the responses of 70 respondents. The results of this study indicate that work Reward has a positive and significant effect on employee performance at PT ISS Indonesia, Indofood Area, Tangerang City, as evidenced by the value of t_calculated > t_table (4.163 > 1.668). This is also supported by a significance value of less than 0.05 (0.000 < 0.05). Punishment also has a positive and significant effect on employee performance at PT ISS Indonesia, Indofood Area, Tangerang City, as indicated by the value of t_calculated > t_table (4.787 > 1.668), and supported by a significance value of less than 0.05 (0.000 < 0.05). Reward and Punishment simultaneously have a significant effect on employee performance at PT ISS Indonesia, Indofood Area, Tangerang City, as evidenced by the value of F_calculated > F_table (20.996 > 3.984), and supported by a significance value of less than 0.05 (0.000 < 0.05).